Symbolic Modeling Counseling Based on Alam Takambang Jadi Guru to Enhance University Students’ Self-Regulated Learning - Hidayat, Hafiz; Handayani, Puji Gusri; Prayitno, Irwan; Ismira, Ismira; Ronvy, Al Shaffaat (Universitas Negeri Padang, 2025)
Many university students exhibit low self-regulated learning, which contributes to various academic challenges. Overcoming this, in this study, the use alam takambang jadi guru as a cultural philosophy has its strength in increasing self-regulated learning. This study aims to test the effectiveness of symbolic modeling with alam takambang jadi guru to improve university students' self-regulated learning. The research was carried out experimentally using a single-subject design. The design used is a baseline–intervention–maintenance approach. The population in this study consists of university students selected using the purposive sampling technique, specifically three individuals who exhibit low self-regulation. The instrument used in this research is a self-regulated learning scale with high reliability and validity. The intervention will be conducted in six sessions, utilizing video media as a symbol. The results of this study showed that the intervention had an effect, with a steady increase in understanding and application that was self-regulated by the students at their university. Thus, university students’ cultural understanding contributed to improvements in self-regulated learning through increased cognitive, motivational, and behavioral knowledge. The conclusions of these findings can be used as a basis for counselors to apply and adopt this technique. Counselors can use this technique by using a group format to reach a large number of university students.